2007
DOI: 10.1007/s10803-007-0402-4
|View full text |Cite
|
Sign up to set email alerts
|

Social Skills Interventions for Children with Asperger’s Syndrome or High-Functioning Autism: A Review and Recommendations

Abstract: This paper reviews the literature examining social skills training (SST) programs for youth with AS/HFA, with an emphasis on critically evaluating efficacy and highlighting areas of future research. The review highlights the disparity between SST programs described in the extant literature, including lack of a universal definition of social skills, various levels of intensity and duration of treatment, divergent theoretical backgrounds, and variety in services provided in clinic or classroom settings. Overall,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
372
2
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 516 publications
(388 citation statements)
references
References 33 publications
5
372
2
9
Order By: Relevance
“…Unfortunately, White et al (2007) noted that many of the gains made during treatment appear to diminish after treatment has concluded. One of the primary factors necessary for social skill maintenance is to help children with ASD generalize the skills learned in treatment to broader contexts (Rao et al 2008). Increased generalization of skills is likely more difficult without systemic changes made during treatment at both the family and parent level.…”
Section: Social Skills Interventions For Asdmentioning
confidence: 99%
“…Unfortunately, White et al (2007) noted that many of the gains made during treatment appear to diminish after treatment has concluded. One of the primary factors necessary for social skill maintenance is to help children with ASD generalize the skills learned in treatment to broader contexts (Rao et al 2008). Increased generalization of skills is likely more difficult without systemic changes made during treatment at both the family and parent level.…”
Section: Social Skills Interventions For Asdmentioning
confidence: 99%
“…In a recent review of social skills training programmes for children with high functioning autism or Aspergers disorder, it was found that 70% of programmes reported success (Rao, Beidel, & Murray, 2008). However, the authors point out that within these successful programmes, success was only for a subset of children or on a subset of skills.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors point out that within these successful programmes, success was only for a subset of children or on a subset of skills. The first limitation Rao et al, (2008) discuss is the lack of a universally accepted definition of social skills and social behaviours thought to be deficient in the children, and therefore requiring intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions for children with social communication difficulties encompass those for children with high-functioning autism spectrum disorders, others aimed at children with language impairments in social interaction but who do not meet the criteria for autism spectrum disorders and school-based interventions that will include (but not specifically target) children with social communication difficulties because they are universal interventions. Recent reviews have examined social skills interventions for children with highfunctioning autism spectrum disorders (Cappadocia & Weiss, 2011;Rao, Beidel, & Murray, 2008) and treatments for disorders of language use in social interactions excluding children with autism spectrum disorders (Gerber, Brice, Capone, Fujiki & Timler, 2012).…”
Section: Interventions For Children With Social Communicative Disordersmentioning
confidence: 99%
“…The study aimed to deal with the limitations of previous studies on children with social communication difficulties (Cappadocia & Weiss, 2011;Gerber et al, 2012;Rao et al, 2008) and included a randomised controlled design with blinded post-test assessment. In addition, the following points were addressed: (a) A carefully sampled group of children using both the TPS to identify the children most at risk from a pool of over 200 and the CCC-2 to describe the profiles of these children; (a) Previous studies have used a variety of methods for sample selection, from clinical diagnoses to universal interventions including all children in a particular class or school.…”
Section: Strengths Of the Studymentioning
confidence: 99%